2022
DOI: 10.3390/sym14122634
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Mixed Np(V)-Ammonium Carbonate

Abstract: This work presents details of the synthesis, properties and structure of a novel neptunium carbonate (NH4)[NpO2CO3], a member of the M[AnO2CO3] (M = K, (NH4), Rb, Cs) class of compounds. Carbonates play an important role in the migration of actinides in the environment, and thus are relevant for handling and disposal of radioactive wastes, including spent nuclear fuel and vitrified raffinates. Knowledge of the crystallographic structure of these compounds is important for models of the environmental migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Structural data on Pu-containing solids are even scarcer than those for Np. However, it has already been shown that the structures of K- and NH 4 + -containing Pu­(V) and Np­(V) mixed carbonates coincide. ,, Consequently, the study of Np­(V) mixed carbonates would help to understand the potential formation and crystal structures of Pu­(V) mixed carbonates with both M­(I) and M­(II) cations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Structural data on Pu-containing solids are even scarcer than those for Np. However, it has already been shown that the structures of K- and NH 4 + -containing Pu­(V) and Np­(V) mixed carbonates coincide. ,, Consequently, the study of Np­(V) mixed carbonates would help to understand the potential formation and crystal structures of Pu­(V) mixed carbonates with both M­(I) and M­(II) cations.…”
Section: Resultsmentioning
confidence: 99%
“…Large cations (K, NH 4 + , etc.) form mixed Np(V) carbonates with a hexagonal neptunyl layer, 18,22,23,27,28 while small cations (Na + and Li + ) form mixed Np(V) carbonates with a orthorombic anionic layer. 21,25 The radius of Ca 2+ (1.00 Å) is close to that of Na + (1.02 Å), supporting this theory.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations